Taking Advantage of Electrostatic Interactions To Grow Langmuir-Blodgett Films Containing Multilayers of the Phospholipid Dipalmitoylphosphatidylglycerol - Aoki, Pedro H. B. [UNESP]; Alessio, Priscila [UNESP]; Rodriguez-Mendez, M. L.; De Saja Saez, J. A.; Constantino, Carlos J. L. [UNESP] (Amer Chemical Soc, 2009)
The use of phospholipids as mimetic systems for studies involving the cell membrane is a well-known approach. In this context, the Langmuir and Langmuir-Blodgett (LB) methods are among the main techniques used to produce ordered layers of phospholipids structured as mono- or bilayers on water subphase and solid substrates. However, the difficulties of producing multilayer LB films of phospholipids restrict the application of this technique depending, on the sensitivity of the experimental analysis to be conducted. Here, an alternative approach is used to produce LB films containing multilayers of the negative phospholipid dipalmitoylphosphatidylglycerol (DPPG). Inspired by the electrostatic layer-by-layer (LbL) technique, DPPG multilayer LB films were produced by transferring the DPPG Langmuir monolayers from the water subphase containing low concentrations of the cationic polyelectrolyte poly(allylamine hydrochloride) (PAH) onto solid substrates. Fourier transform infrared (FTIR) absorption spectroscopy revealed that the interactions between the NH(3)(+) (PAH) and PO(4)(-) (DPPG) groups might be the main driving forces that allow growth of these LB films. Besides, ultraviolet-visible (UV-vis) absorption spectroscopy showed that the multilayer LB films can be grown in a controlled way in terms of thickness at nanometer scale. Cyclic voltammetry showed that DPPG and PAH are more packed in the LB than LbL films. The latter finding is related to the distinct molecular architecture of the films since DPPG is structured as monolayers in the LB films and multilamellar vesicles in the LbL films, Despite the interaction with PAH, cyclic voltammetry also showed that DPPG retains its biological activity in LB films, which is a key factor since this makes DPPG a suitable material in sensing applications. Therefore, multilayer LB films were deposited onto Pt interdigitated electrodes forming sensing units, which were applied in the detection of a phenothiazine compound [methylene blue (MB)] using impedance spectroscopy. The performance of DPPG in single-Layer and multilayer LB films was compared to the performance of sensing unities composed of DPPG in single-layer and multilayer LbL films, showing the importance of both the thickness and the molecular architecture of the thin films. As found in a previous work for LbL films, the high sensitivity reached by these sensing units is intimately related to changes in the morphology of the film its evidenced by the micro-Raman technique. Finally, the interaction between MB and the (DPPG + PAH) LB films was complemented by pi-A isotherms and surface-enhanced resonance Raman scattering (SERRS).